Enhanced γ-Glutamyltranspeptidase Imaging That Unravels the Glioma Recurrence in Post-radio/Chemotherapy Mixtures for Precise Pathology via Enzyme-Triggered Fluorescent Probe - Shi, Ben; Zhang, Zhenyu; Lan, Chuanjin; Wang, Bao; Xu, Shangchen; Ge, Mingxu; Xu, Ge; Zhu, Tianli; Liu, Yingchao; Zhao, Chunchang (Frontiers in Neuroscience, 2019)
Accurate pathological diagnosis of gliomas recurrence is crucial for the optimal management and prognosis prediction. The study here unravels that γ-glutamyltranspeptidase (GGT) fluorescence probe imaging in twenty recurrent glioma tissues selectively recognize the most malignant portion from treatment responsive tissues induced by radio/chemo-therapy (Figure 1). The overexpression of GGT in recurrent gliomas and low level in radiation necrosis were validated by western blot analysis and immunohistochemistry. Furthermore, the ki-67 index evaluation demonstrated the significant increase of malignancy aided by GGT-responsive fluorescent probe to screen out the right specimen through fast enhanced imaging of enzyme activity. Importantly, our GGT-targeting probe can be used for accurate determination of pathologic evaluation of tumor malignancy, and eventually for guiding the following management in patients with recurrent.